Persistent anterograde amnesia due to the artery of Percheron occlusion: a case report. Issue 2 (4th March 2018) - Ince, Birsen; Asan, Furkan
ABSTRACT: Bilateral thalamic infarction involving the artery of Percheron (AOP) can cause diagnostic difficulties due to the varying clinical presentations. AOP infarcts presented with isolated memory impairment are not common and the factors affecting the persistence of memory disorders are still unknown. A 41-year-old male patient was hospitalized with acute unconsciousness. MRI disclosed bilateral paramedian thalamic infarction The patient had isolated memory deficit and his anterograde amnesia continued without any change in the past decade. More cases might answer the questions concerning the intra- and extra-thalamic structures responsible for the amnesic syndrome and the factors affecting the persistence of the symptoms.